Blood of Others : Stalin's Crimean Atrocity and the Poetics of Solidarity - Finnin, Rory (Book collections on Project MUSE., 2022)
"Blood of Others offers a cultural history of Crimea and the Black Sea region, one of Europe's most volatile flashpoints, by chronicling the aftermath of Stalin's 1944 deportation of the Crimean Tatars in four different literary traditions."--